Frozen IVF Cycles to Circumvent the Hormonal Storm on Endometrium. (April 2020) - Viganò, Paola; Alteri, Alessandra; Busnelli, Andrea; Vanni, Valeria Stella; Somigliana, Edgardo
Abstract : Controlled ovarian hyperstimulation (COH) determines an anticipation of endometrial maturation and a premature occurrence of the implantation window, as shown by histological, histochemical, and molecular studies and indirectly by clinical trials. There is growing agreement that in patients hyper-responding to COH and in those undergoing transfer at the blastocyst stage, deferring the transfer in a subsequent frozen cycle could increase pregnancy outcomes. For blastocysts, implantation after a fresh transfer may be limited as the implantation window is already closed while, in hyper-responders to COH, the anticipation magnitude could be more marked thus hampering implantation also for cleavage-stage embryos. Research should focus in depth on pregnancy outcomes and on the most suitable modality to prepare the endometrium for frozen transfers. Highlights: Controlled ovarian hyperstimulation (COH) determines an anticipation of endometrial maturation and a premature occurrence of the implantation window, as demonstrated by histological and molecular findings. Deferring embryo transfer in a subsequent non-stimulated cycle can circumvent the detrimental effects of the supraphysiological levels of sex hormones on endometrial receptivity as the overall chance of live birth associated with the strategy is significantly improved. The magnitude of endometrial anticipation induced by COH may vary with more severe consequences for the implantation outcome in patients with an early rise of progesterone and in those responding more to COH. Different regimens for endometrial preparation for frozen embryo transfers are similar in terms of pregnancy outcomes but the risk of preeclampsia is increased in women treated with hormone replacement therapy.